FOLLOW THE MASTER: REFLECTIONS ON DANCE, IMITATION AND EARLY CHILDHOOD EDUCATION - Almeida, Fernanda De Souza [UNESP] (Univ Fed Rio De Janeiro, Fac Letras, 2017)
This article reflects on imitation as a chance to work dance with small kids. To this end, it presents dialogues between cuttings from two studies that deal with the educational praxis: the master's thesis from Almeida (2013) and the Dancarelando extension project. Both are characterized by research-actions with data collected in daily camps and faced with the theory to identify the results. The study of these proposals revealed that imitation is appropriate, particularly if linked to pretend; however it is necessary that does not prevent the re-elaboration of experience. Thus, this paper aims to contribute to the training of teachers, through practical experience in dance sharing, meeting with current public policies.
Keywords: Dance; Child education; Educational Praxis